1978
DOI: 10.1139/z78-350
|View full text |Cite
|
Sign up to set email alerts
|

Effect of salinity on the osmoregulatory cells in the tracheal gills of the stonefly nymph, Paragnetina media (Plecoptera: Perlidae)

Abstract: The ultrastructure of the osmoregulatory cells in the integument of the stonefly nymph, Paragnetina media, shows changes in media hypotonic, isotonic, and hypertonic to the hemolymph. Exposure to hypotonic concentration results in an increase in the plasma membrane folds, mitochondria, and microtubules in the cytoplasm. In isotonic and hypertonic concentrations, the cells show cellular disorganization and apparent loss in their function. These results suggest that the structural changes in the osmoregulatory c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1980
1980
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 7 publications
1
11
0
Order By: Relevance
“…Ion regulation was disrupted by damage to the osmoregulatory cells of nymphs exposed to pH 2 .5, and subtle changes occurred in osmoregulatory cells of nymphs exposed to pH 4 .0 . Kapoor (1978) found that similar changes in ion content occurred in plecopteran nymphs exposed to a hypertonic, 1 .2% sodium chloride solution . Similarly, ionoregulation imbalance probably occurred in damselfly nymphs at pH 3 .5 in our study.…”
Section: Predation By Nymphs Cultured In Pond Water Vs Rswmentioning
confidence: 65%
“…Ion regulation was disrupted by damage to the osmoregulatory cells of nymphs exposed to pH 2 .5, and subtle changes occurred in osmoregulatory cells of nymphs exposed to pH 4 .0 . Kapoor (1978) found that similar changes in ion content occurred in plecopteran nymphs exposed to a hypertonic, 1 .2% sodium chloride solution . Similarly, ionoregulation imbalance probably occurred in damselfly nymphs at pH 3 .5 in our study.…”
Section: Predation By Nymphs Cultured In Pond Water Vs Rswmentioning
confidence: 65%
“…This group was largely composed of small ephemeral pools associated with old trackways on the Lizard, which are characterised by relatively high conductivities due to their mineral substrate being derived from serpentine bedrock (see Bilton et al, 2009). The influence of conductivity on macroinvertebrate community composition and diversity is well documented (Kapoor, 1978;Lemly, 1982;Williams et al, 1997;Williams and Williams, 1998;Blasius and Merritt, 2002;Biggs et al, 2005;De Jonge et al, 2008), and at low values, the vast majority of studies document a positive relationship between conductivity and species richness. Very high conductivities are associated with a decline in the diversity of freshwater macroinvertebrates, this operating largely through the osmotic challenges of high ion concentrations (Macan, 1974;Blasius and Merritt, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The three-dimensional SEM images were related to the two-dimensional images of thin sections from the proximal, middle, and distal regions of the tubule. All material for both SEM and transmission electron microscopy (TEM) was fixed in 2.5% glutaraldehyde in phosphate buffer (pH 7.1 ) and postfixed in 1 % osmium tetroxide (Kapoor 1978). For SEM, critical-point-dried Malpighian tubules, both whole and fractured in different planes, were mounted on stubs and coated with about 100 A ( 1 A = 0.1 nm) of gold.…”
Section: Methodsmentioning
confidence: 99%
“…The present study was undertaken to invesOsmoregulatory mechanisms in the stoneflies (Plecoptera) figate the stmctural details and cell types of the Malpighian are of interest, as the majority spend most of their life in fresh in this !jtonefly water. The 300 mosmol/L osmotic concentration of the hemolymph of nymphs of Paragnetina media is extremely hyperosmotic with respect to fresh water (Kapoor 1978). These nymphs are faced with the problems of ion losses to the surrounding water and dilution of the body fluids because of continual diffusion of water through the body surface.…”
Section: Introductionmentioning
confidence: 99%